(3TQM TeSjI GdMSGHs - (3CHh ESMGb Hf YHO Gddg GdcOSGfis; (3GdfXGe GdfjSGHhQj , GdMSf Hf eMeO Hf GdMSjf Gdbej GdfjSGHhQj, fXGe GdOjf GdCYQL,J (B850 (3g` s
(3ChdgG (B:s
(3fMeOc Gddge Ydi eG bSeJ dfG ef VQhH GfYGe dGjMUi YOOgG hHYO aEfi WGdeG cfJ YGRekG Ydi Cf GcJH Ke QCjJ GdfGS Edi TeSjI GdMSGH QGZHjf s
(3BNQgG (B:s
(3ajfUa GdNeSI hROJ Ydjg NeSI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3GfXQg eY GdeNWhW Qbe (B117 (3ef faS GdHYKIs
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai c X (B2 / 1062 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B216 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B281s
Keywords: (3GdQjGVjGJs